Raven Head Element - Paula Wesley (1976- ) (2010)
Raven head design in black and red acrylic paint, on coloured, speckled paper. Excellent condition. FDSNCA Graduate 2012. Located in FDSNCA. Copyright held by artist. Photograph by Highlight Studio.